Martin's physical pharmacy and pharmaceutical sciences - Sinko, Patrick J. (Lippincott Williams & Wilkins, 2017)
Martin's Physical Pharmacy and Pharmaceutical Sciences is considered the most comprehensive text available on the physical, chemical, and biological principles that underlie pharmacology. This 7th Edition puts a stronger focus on the most essential, practical knowledge, and is updated to reflect the broadening scope and diversity of the pharmaceutical sciences